Mechanical properties of cement brick using rice husk ash (RHA) as cement replacement - Izzat Akmal, Ruslee (2017)
This research is to determine the characteristic of cement sand brick in term of compressive strength, flexural strength and water absorption using rice husk ash as a partially cement replacement. Cement bricks containing rice husk ash should be promoted as a new construction material to replace the existing bricks in market. Properties of the material used must be better understood first to obtain the desired cement brick. Generally, this paper presents a laboratory study on the effect of rice husk ash (RHA) on properties of cement bricks. The compressive strength, flexural strength and water absorption were investigated. Preliminary analysis of the constituent materials of the ordinary Portland cement and Rice Husk Ash cement bricks were conducted to confirm their suitability for bricks making. Physical test of the recently prepared mix was also carried out. 210mm x 100mm x 75mm cement bricks were cast and compacted for 7, 14 and 28 days at 0, 10, 20 and 30 percent replacement levels. In conclusion, the high performance of bricks can be produced using rice husk ash (RHA) as cement replacement material. The compressive strength of the OPC and RHA cement bricks increases with age at curing and decreases as the percentage of RHA content increases. The study arrived at an optimum replacement level of 20%.